2015
DOI: 10.1016/j.schres.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of schizophrenia-related genes in the forebrain of adolescent and adult rats exposed to maternal immune activation

Abstract: Maternal immune activation (MIA) is an environmental risk factor for schizophrenia, and may contribute to other developmental disorders including autism and epilepsy. Activation of pro-inflammatory cytokine systems by injection of the synthetic double-stranded RNA polyriboinosinic-polyribocytidilic acid (Poly I:C) mediates important neurochemical and behavioral corollaries of MIA, which have relevance to deficits observed in schizophrenia. We examined the consequences of MIA on forebrain expression of neuregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 109 publications
(151 reference statements)
0
18
0
Order By: Relevance
“…Animals were housed under standard conditions with access to food and water ad libitum . The Poly I:C treatment protocol was performed as previously described (Bronson et al, 2011; Hemmerle et al, 2015). Briefly, on gestational day 14 pregnant dams were injected with Poly I:C (8 mg/kg i.p.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Animals were housed under standard conditions with access to food and water ad libitum . The Poly I:C treatment protocol was performed as previously described (Bronson et al, 2011; Hemmerle et al, 2015). Briefly, on gestational day 14 pregnant dams were injected with Poly I:C (8 mg/kg i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Semi-adjacent sections were processed for the in situ hybridization localization of GAD 67 mRNA using a 35 S-labeled cDNA probe, as previously described (Seroogy and Herman, 1997; Hemmerle et al, 2012, 2015; Makinson et al, 2015). Briefly, slides were pretreated, dehydrated and delipidated prior to hybridization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, we can refer to neurocircuitry development that is better understood; prefrontal fast-spiking interneurons do not mature until late adolescence (Tseng and O'Donnell, 2007), therefore the deleterious effects of immune insults to cortical function may not become evident until the transition through adolescence. Additionally, recent data have illustrated that prenatal immune activation alters the expression of genes for neurotrophic and neurodevelopmental regulators within the prefrontal cortex, but these expression changes were not seen prior to adolescence (Hemmerle et al, 2015). These findings further suggest that the effects of neuro-immune events leading to schizophrenia might manifest during a period of rapid and critical development of the prefrontal cortex.…”
Section: Psychiatric Disorders With An Adolescent Onset: Adding Thmentioning
confidence: 99%
“…Increasing evidence supports a role of immune activation as a prominent causative factor in the pathogenesis of a number of major neuropsychiatric disorders as well (Hemmerle et al, ). Consistent with this notion, recent studies have demonstrated that the inflammasome modulates initial neuroinflammatory processes at the initial stage, with secondary events inclusive of oxidative stress that have been shown to activate the inflammasome (Kim et al, ).…”
Section: Introductionmentioning
confidence: 99%